2019
DOI: 10.1016/j.agwat.2018.11.024
|View full text |Cite
|
Sign up to set email alerts
|

A coupled model for simulating water flow and solute transport in furrow irrigation

Abstract: A B S T R A C TFor optimal water and fertilizer management under furrow irrigation, it is important to understand the water and solute dynamics on the land surface and in the subsurface. An efficient mathematical tool is required to describe these dynamic processes. We propose a coupled model in which surface water flow and solute transport are described using the zero-inertia equation and the average cross-sectional convection-dispersion equation, respectively, while the two-dimensional Richards equation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The subsurface flow of water in this study was simulated using HYDRUS 2D/3D, previously shown to successfully simulate the two-dimensional subsurface water flow from irrigation furrows (e.g., Ebrahimian et al [10], Deb et al [11], Šimůnek et al [12], Liu et al [13], and Bristow et al [14]).…”
Section: Numerical Computationsmentioning
confidence: 99%
“…The subsurface flow of water in this study was simulated using HYDRUS 2D/3D, previously shown to successfully simulate the two-dimensional subsurface water flow from irrigation furrows (e.g., Ebrahimian et al [10], Deb et al [11], Šimůnek et al [12], Liu et al [13], and Bristow et al [14]).…”
Section: Numerical Computationsmentioning
confidence: 99%
“…In the literature, studies on infiltration modeling in surface irrigation can be found; for example, Liu et al [2] proposed a coupled model in which surface water flow and solute transport are described using the zero-inertia equation and the average cross-sectional convection-dispersion equation, respectively, while the two-dimensional Richards' equation and the convection-dispersion equation are used to simulate water flow and solute transport in soils, respectively. Dong et al [3] developed a new numerical methodology based on the physical-based model of surface irrigation and the Monte Carlo simulation method to improve the modeling accuracy of surface irrigation performance at a field scale.…”
Section: Introductionmentioning
confidence: 99%